Evaluasi Pemahaman dan Kinerja Pengguna Data iSIKHNAS - Bili, Feny A. L.; Neolaka, Melkisedek N. B. C.; Telupere, Franky M. S. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2022)
The national animal health information system (iSIKHNAS) aims to provide data related to animal health and present it to relevant stakeholders that can be utilized for the benefit of the community. The iSIKHNAS system can run well if there is an appropriate understanding by its users. This study aims to analyze the understanding of users (animal health officers) in the iSIKHNAS application system to improve the performance of animal health services. The research method used is to collect information or data and conduct an investigation on the data that has been obtained related to the level of understanding of iSIKHNAS users. Based on the information obtained, there is a phenomenon that illustrates that the understanding of officers related to iSIKHNAS has decreased, and the phenomenon of using the iSIKHNAS application is only to report service activities. The decrease in the level of understanding of users of the iSIKHNAS application can be caused by the lack of participation in new training and refresher training to update the knowledge of users.